ESTIMASI POTENSI DAN NILAI EKONOMIS PUPUK KANDANG DI BALI - -, SUHARYANTO; RINALDI, JEMMY (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
The potential of dry land area for agricultural is quite big. The advantages of manure as an alternative it could be possible since the number of livestock such as cow, chicken and goat is quite potential. The total production of solid manure in 2001 are 1.313.794,12 metric ton cow manure, 284.484,35 metric ton chicken manure and 33.374,28 metric ton goat manure. This amount can be used 25 percent dry land area in Bali and give surplus 100 percent of fishpond area. The contributions of Nitrogen, Phosphate and Kalium for every category that produce from cow manure are 3.673,3 metric ton N, 2.626,7 metric ton P2O5 and 1.309,2 metric ton K2O. Chicken manure contributes 1.988,6 N, 2.275,2 metric ton P2O5 and 1.133,9 metric ton K2O and goat manure contains 212, 3 metric ton N, 166, 6 metric ton K2O and 149, 5 metric ton K2O. If we compare the manure with chemical fertilizers it is similar with 3.265.11 metric ton Urea, 6.912.42 metric ton SP-36 and 2.380.29 metric ton KCl for cow manure. The production of Chicken manure is equal to 1.767.60 metric ton urea, 5.987.34 metric ton SP-36 and 2.984.07 metric ton KCl and for goat manure is equal to 488.664 metric ton urea, 701.970 metric ton SP-36 and 271.789 metric ton KCl.
Keywords: livestock’s manure, cow, chicken and goat